Microbial diversity gradients in the geothermal mud volcano underlying the hypersaline Urania Basin - Lazar, Cassandre Sara; Schmidt, Frauke; Elvert, Marcus; Heuer, Verena B.; Hinrichs, Kai-Uwe; Teske, Andreas P. (Frontiers in Microbiology, 2022)
Urania Basin, a hypersaline seafloor basin in the Mediterranean, harbors a mud volcano that erupts fluidized mud into the brine. Sampling the brine fluid, fluid mud layers, and subsurface sediments at the bottom of the mud volcano, provided an opportunity to investigate the complete sequence of bacterial and archaeal communities of the Urania Basin brine, fluid mud layers and subsurface sediments. The bacterial and archaeal communities show characteristic, habitat-related trends as they change throughout the sample series, from extremely halophilic bacteria (KB1) and archaea (Halodesulfoarchaeum spp.) in the brine, towards moderately halophilic and thermophilic endospore-forming bacteria and uncultured archaeal lineages in the mud fluid, and finally ending in aromatics-oxidizing bacteria, uncultured spore formers, and heterotrophic subsurface archaea (Thermoplasmatales, Bathyarchaeota and Lokiarcheota) in the deep subsurface sediment at the bottom of the mud volcano. Since most bacterial and archaeal lineages are anaerobic heterotrophic fermenters, the layered brine and mud volcano microbial ecosystem functions as a layered fermenter for organic, petroleum-enriched carbon degradation. However, no cultured methanogens were detected, leaving an uncultured euryarchaetoal lineage (MSBL1) as the best candidate for methanogenic terminal degradation of organic matter. The frequent detection of spore-forming, thermophilic Firmicutes in the fluid mud layer suggests that the Urania Basin mud volcano provides a source of endospores that inoculate cold seafloor sediments.